The Effect of Concentration Factor on Membrane Fouling - Appana Lok; Pierre R. Bérubé; Robert C. Andrews (Membranes, 2017)
Bench-scale systems are often used to evaluate pretreatment methods and operational conditions that can be applied in full-scale ultrafiltration (UF) systems. However, the membrane packing density is substantially different in bench and full-scale systems. Differences in concentration factor (CF) at the solution–membrane interface as a result of packing density may impact the mass transfer and fouling rate and the applicability of bench-scale systems. The present study compared membrane resistance when considering raw water (CF = 1) and reject water (also commonly referred to as concentrate water) (CF > 1) as feed in UF systems operated in deposition (dead-end) mode. A positive relationship was observed between the concentration of the organic matter in the solution being filtered and resistance. Bench-scale trials conducted with CF = 1 water were more representative of full-scale operation than trials conducted with elevated CFs when considering membrane resistance and permeate quality. As such, the results of this study indicate that the use of the same feed water as used at full-scale (CF = 1) is appropriate to evaluate fouling in UF systems operated in deposition mode.